(untitled) (Tarbiyah Suska Conference Series, 2022)
It was Research and Development with ADDIE (Analysis, Design, Development, Implementation, Evaluation) model aiming at developing Discovery Learning based student worksheet on Two Variable Linear Equations System material in facilitating student mathematical problem-solving ability meeting valid, practical and effective criteria. This research was administered at Private Islamic Junior High School of Miftahul Jannah Peranap. The subjects of this research were educational technology and learning material experts who were lecturers, Mathematics subject teachers, and the eighth-grade students. The object was Discovery Learning based student worksheet on Two Variable Linear Equations System material in facilitating student mathematical problem-solving ability. Questionnaire and test were the techniques of collecting data. The instruments of collecting data were validity questionnaire sheet, practicality questionnaire sheet, and posttest question sheet. The data were quantitative and qualitative. The data obtained were analyzed by using qualitative descriptive and quantitative analysis techniques. Based on data analyses, (1) Discovery Learning based student worksheet was stated on very valid category with aiken index score 0,915, (2) Discovery Learning based student worksheet was stated on very practical category with percentage 88.86%, and (3) Discovery Learning based student worksheet was stated on effective category. Based on these findings, the student workbook developed was valid, practical, and effective.